Can we effectively degrade microcystins? - implications on human health - Hiskia, Anastasia E.; Pelaez, Miguel A.; Song, Weihua; O’Shea, Kevin E.; De La Cruz, Armah A.; He, Xuexiang; Dionysiou, Dionysios Demetriou D.; Antoniou, Maria G. (My University, 2011)
Microcystins are cyclic heptapeptide toxins produced by a number of genera of cyanobacteria. They are ubiquitous in bodies of water worldwide and pose significant hazard to human, plant, and animal health. Microcystins are primarily hepatotoxins known to inhibit serine-threonine phosphatases leading to the disruption of cascade of events important in the regulation and control of cellular processes. Covalent binding of microcystins with phosphatases is thought to be responsible for the cytotoxic and genotoxic effects of microcystins. In addition, microcystins can trigger oxidative stress in cells resulting in necrosis or apoptosis. Their cyclic structure and novel amino acids enhance their stability and persistence in the environment. Humans are primarily exposed to microcystins via drinking water consumption and accidental ingestion of recreational water. Recreational exposure by skin contact or inhalation to microcystins is now recognized to cause a wide range of acute illnesses which can be life-threatening. Microcystins are primarily degraded by microorganisms in the environment, while sunlight can cause the isomerization of the double bonds and hydroxylation in the presence of pigments. Attempts to utilize these organisms in sand and membrane filters to treat water contaminated with microcystins showed complete removal and detoxification. Conventional water treatment processes may not fully eliminate microcystins when there are high levels of organic compounds especially during harmful bloom events. Combination of conventional and advanced oxidation technologies can potentially remove 100% of microcystins in water even in turbid conditions. This review covers selected treatment technologies to degrade microcystins in water
Keywords: Biodegradation; Degradation; Hydroxyl radicals; Ozone; Photolysis; Sonolysis; Sulfate radicals